2002
DOI: 10.1086/341140
|View full text |Cite
|
Sign up to set email alerts
|

The Variability of the Hgiiλ3984 Line of the Mercury‐Manganese Star α Andromedae

Abstract: The variability of the Hg ii 3984 line in the primary of the binary star And was discovered through the examination of high-dispersion spectra with signal-to-noise ratios greater than 500. This first definitively identified spectrum variation in any mercury-manganese star is not due to the orbital motion of the companion. Rather, the variation is produced by the combination of the 2.38236 day period of rotation of the primary that we determined and a nonuniform surface distribution of mercury that is concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
95
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(100 citation statements)
references
References 27 publications
5
95
0
Order By: Relevance
“…As can be seen in Fig. 4, the Ti abundance does not exhibit a distinct ring structure around the stellar equator as was found for the Hg distribution in the HgMn star αAnd (Adelman et al 2002). The maps in general show a surface abundance that is higher than the solar abundance of Ti, −7.02, and have an average abundance of −6.47.…”
Section: Surface Chemical Inhomogeneities By Doppler Imaging Reconstrsupporting
confidence: 59%
See 1 more Smart Citation
“…As can be seen in Fig. 4, the Ti abundance does not exhibit a distinct ring structure around the stellar equator as was found for the Hg distribution in the HgMn star αAnd (Adelman et al 2002). The maps in general show a surface abundance that is higher than the solar abundance of Ti, −7.02, and have an average abundance of −6.47.…”
Section: Surface Chemical Inhomogeneities By Doppler Imaging Reconstrsupporting
confidence: 59%
“…The first indication of variability of the Hg ii 3984 Å and Y ii 3983 Å lines was reported for the HgMn SB2 system AR Aur by Takeda et al (1979). Later, Wahlgren et al (2001) and Adelman et al (2002) showed that the Hg ii 3984 Å line of the primary component of α And varies with a 2.8-d period. The spectral line variations were attributed to the surface inhomogeneous mercury distribution along the stellar equator, together with the stellar rotation period.…”
Section: Introductionmentioning
confidence: 99%
“…There is not a good explanation of this behavior. Recently, this line's profile in the HgMn star α And A was found to be peculiar (Ryabchikova et al 1999) and later periodically variable (Adelman et al 2002), the first known example of spectral variability among the HgMn stars. The most likely interpretation of this variability is an inhomogeneous Hg surface distribution combined with the 2.382 day stellar rotation period.…”
Section: Discussionmentioning
confidence: 98%
“…For example, exploratory calculations by Seaton (1996) using Opacity Project data suggest that their manganese rich atmospheres are a time variable surface result of radiatively-driven diffusion deep in the stellar envelope. Adelman et al (2002) reported the first spectrum variability in Tables 4-8 are only available in electronic form at the CDS via anonymous ftp to cdsarc.u-strasbg.fr (130.79.128.5) or via http://cdsweb.u-strasbg.fr/cgi-bin/qcat?J/A+A/447/685 this stellar class of Hg II λ3984 in α And A, a discovery whose implications are still just being explored (see, e.g., Kockukhov et al 2005). With results from many stars one can look at the dependences on stellar parameters and make comparisons with theoretical predictions (see, e.g., Adelman et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…HgMn stars are frequently found in binaries and lie on the H-R diagram between the early-A and late-B spectral types, which corresponds to T eff = 9500 − 16000 K. A number of studies during the last decade reported variability of some spectral lines, indicating the presence of chemical spots in HgMn stars (Adelman et al 2002, Kochukhov et al 2005, Hubrig et al 2006. It is believed that the presence of magnetic field is necessary for creating inhomogeneities in stellar atmospheres.…”
Section: Introductionmentioning
confidence: 99%